Mixed Fungal Infection of Phaeohyphomycosis and Aspergillosis involving Right Maxillary Sinus in a Newly Diagnosed Case of Diabetes Mellitus (GAIMS Journal of Medical Sciences, 2023)
Phaeohyphomycosis is an infection due to dematiaceous fungi which usually involve the skin and subcutaneous tissue. Phaeohyphomycosis in subcutaneous location has presentation in the form of nodules, papules ulcerated plaques, verruca-like hyperkeratotic plaques, cystic lesions, abscess formation, pyo-granuloma, discharging sinuses, non-healing ulcers. Brown-walled hyphae in the epidermis and dermis are its hallmark. Aspergillosis is ubiquitous, invasive fungal infection in diabetics and immunocompromised hosts. Here, we are reporting a mixed fungal infection of right maxillary sinus in a newly diagnosed case of diabetes mellitus.